The Use of Word Mapping Strategy in Teaching Vocabulary to Class VIII at MTsN Masamba - Muh. Hardiansyah S; Reski Yusrini Islamiah Yunus; . Andi Mangnguntungi Sudirman (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This study examined the effectiveness of a word mapping strategy in teaching English vocabulary to eighth-grade students at MTsN Masamba. A pre-experimental one-group pre-test-post-test design was employed. The population comprised 48 eighth-grade students, and 17 students from class VIII A were selected as the sample. The instrument was a 15-item multiple-choice vocabulary test administered before and after four treatment sessions. During the treatment, students constructed word maps from familiar themes, pictures, descriptive texts, and word relationships. The mean score increased from 64.82 on the pre-test to 84.59 on the post-test, representing a mean gain of 19.76 points. Fifteen students obtained higher scores, two obtained equal scores, and none obtained lower scores. Because the post-test scores did not meet the normality assumption, the Wilcoxon signed-rank test was applied. The test produced Z = -3.417 and p = .001, indicating a statistically significant difference between the pre-test and post-test results. The findings suggest that word mapping can improve vocabulary achievement while encouraging students to participate actively, connect new words with prior knowledge, and organize word meanings visually.